2021
DOI: 10.3390/nu13082763
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Intake of Energy and Nutrients Is Common in Older Family Caregivers

Abstract: The aim of this study was to investigate the nutritional status, determinants of nutritional status, and adequacy of energy and nutrient intake of older family caregivers (FC). Nutritional status was measured using the Mini Nutritional Assessment (MNA), plasma albumin, plasma pre-albumin, and blood hemoglobin concentrations. Dietary intake was assessed with a three-day food record. Comorbidity (B −0.283, 95% CI: −0.492, −0.073), quality of life (B 0.045, 95% CI: 0.018, 0.072) and energy intake (B 0.001, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“… 26 Recently, a study showed a large number of elderly were malnourished. 27 due to decreased physical performance, 28 decline in cognition, 29 poor oral health, 30 and dysphagia. 31 Especially, another interesting study also points out ALB is a risk factor for aspiration pneumonia and can be monitored for aspiration pneumonia management post operation, confirming the close association between ALB and pneumonia-related prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Recently, a study showed a large number of elderly were malnourished. 27 due to decreased physical performance, 28 decline in cognition, 29 poor oral health, 30 and dysphagia. 31 Especially, another interesting study also points out ALB is a risk factor for aspiration pneumonia and can be monitored for aspiration pneumonia management post operation, confirming the close association between ALB and pneumonia-related prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from FC registers of Kuopio and Vesanto between April 2019 and October 2019. The recruitment process of this study has been described previously [ 7 ]. All the participants had a valid care allowance (CA) during their participation in the 6-month intervention (6 months) and the 6-month follow-up (12 months) between June 2019 and December 2020.…”
Section: Methodsmentioning
confidence: 99%
“…FCs are also more vulnerable to the risk of malnutrition than other community-dwelling older people without a CR [ 5 ]. Insufficient dietary intake is common among older FCs [ 6 , 7 ], although sufficient dietary intake has many benefits for older people. For example, optimal intake of nutrients can prevent frailty [ 8 ], and optimal protein intake can prevent the decline of physical performance [ 9 ] and improve lean body mass [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers help improve the health conditions and quality of life of their care recipients and can prevent or delay institutionalisation [4]. However, some FCs have health vulnerabilities, possibly affecting their ability to provide care [5][6][7].…”
Section: Introductionmentioning
confidence: 99%